Nutritional and physical requirements for mycelial growth of Agocybe cylindracea (DC. Fr.) Maire - Cabanting, Rosa Mia; Kalaw, Sofronio P.; Reyes, Renato G. (2011)
Agocybe cylindracea is a widely distributed edible mushroom that usually grows in fallen logs and agricultural wastes. This mushroom has great potential in the nutriceutical and pharmaceutical industries because of its hypoglycaemic effects, anti-carcinogenic activity and antioxidant property. Although this mushroom is successfully cultivated in Japan and Taiwan, the production technology under Philippine condition has not yet been developed. The results generated from this study will serve as benchmark information for the development of production technology for growing this mushroom. The research team evaluated different indigenous materials and physical factors (pH, aeration and illumination) and different grain materials for efficient and luxuriant mycelia growth and proliferation. Among the different indigenous culture media evaluated, sorgum sucrose gulaman registered very thin and widest mycelia diameter with a mean of 82.67 mm after 8 days of incubation while corn frit glucose gulaman recorded very thin and smallest mycelia diameter with a mean of 40.67 mm. Moreover, coconut water gulaman is the most suitable medium for optimum mycelia growth with a mean mycelia diameter of 64 mm. Results further showed that A. cylindracea cultured on coconut water gulaman at pH 6 incubated in sealed and alternating light and dark conditions favoured the mycelia growth and proliferation. Meanwhile, among the grains evaluated for mass production of fruiting bags, sorghum seeds recorded the shortest incubation period with a mean of 14 days while rice seeds had the longest incubation period with a mean of 41.33 days.
Keywords: Edible mushrooms